A case of appendiculo-ileal knotting as a cause of gangrenous small bowel obstruction in a 64-year-old man in a Government Hospital, West Bengal, India - Mandal, Mohit Kumar; Sarkar, Niladri; Sarkar, Sudip; Mollah, Jamsed (International Surgery Journal, 2025)
Appendiculo-ileal knotting is an extremely rare cause of mechanical small bowel obstruction (SBO), characterized by the appendix wrapping around the ileum, leading to obstruction, ischemia, and potential bowel gangrene. Preoperative diagnosis is challenging due to its rarity and nonspecific clinical presentation. A 64-year-old male presented with acute abdominal pain, progressive distension, and inability to pass stool and flatus. Imaging showed features of SBO, and exploratory laparotomy revealed a mucocele of the appendix forming a tight knot around the ileocecal junction. This caused gangrene of the cecum and a segment of the ileum. Surgical intervention included a limited right hemicolectomy, excision of the appendix, and the creation of a double-barrel stoma. Postoperative recovery was uneventful, and the patient was discharged in stable condition. Appendiculo-ileal knotting represents a rare yet serious etiology of SBO. Its pathophysiology involves an inflamed and mobile appendix encircling the ileum. Diagnosis often requires surgical exploration, and timely intervention is critical to prevent complications such as gangrene and perforation. This case highlights the importance of considering appendiculo-ileal knotting in atypical presentations of SBO. Prompt surgical management is essential to improve outcomes and prevent life-threatening complications.